An Organizational Approach to Addressing Racism in Orthopaedic Surgery: AOA Critical Issues Symposium. (19th October 2022) - Brooks, Jaysson T.; Dixon, Tonya; Simpson Mason, Bonnie; Archdeacon, Michael
Abstract: This article highlights the key topics that were presented at a symposium of the American Orthopaedic Association in May 2021, with the primary objectives of acknowledging the existence of systemic racism within the field of orthopaedic surgery, developing a plan for combating racism before it manifests within orthopaedic departments and practices, and understanding the benefit of pipeline programs in diversifying the orthopaedic surgeon workforce. When the word racism is mentioned among a group of orthopaedic surgeons, it may have the immediate effect of stifling honest conversations. Therefore, the crippling effects of racism within orthopaedic surgery are not addressed, and there are downstream effects that influence patient care by perpetuating disparities in health care. If orthopaedic departments want to fix the lack of diversity within the specialty, the magnitude of the problem must first be measured. Fortunately, through the efforts of the J. Robert Gladden Orthopaedic Society, data sets are being created that better measure the diversity of individual orthopaedic residency programs. In addition to hiring diverse faculty, orthopaedic departments and practices should focus on the mentorship, sponsorship, retention, and promotion of these faculty. Finally, pipeline programs such as Nth Dimensions have a proven track record for improving the diversity of the orthopaedic workforce and can serve as the primary mechanism employed by departments and practices in making their orthopaedic surgeon workforce look more like the demographics of the United States.